"Every time, they took more from us": Privatization and Telecommunications Workers in Rural Argentina, 1969–2000. (2022) - Brudney, Edward
Abstract: This article analyzes the lasting effects of privatization on public-sector telecommunications workers in Argentina's rural interior. I draw on over fifty hours of oral histories carried out from 2015 to 2017 with former ENTel and Telefónica workers in General Pico, in the interior province of La Pampa, Argentina. This unique source base reveals how the material objects themselves acquired symbolic weight in the minds of workers, and how the introduction of new technologies and labor regimes after privatization in 1990 eroded workers' feelings of loyalty toward and ownership over the previously state-run company. This article specifically explores notions of trauma as related to the destruction of the physical materials of work, and the association between that destruction and the mass layoffs that followed. David Harvey's engagement with creative destruction in late capitalism has suggested that "continuous innovation"—whether technological or practical—has meant the devaluation and/or destruction of existing labor relations. I expand this concept to show how this logic of "creative destruction" maps onto spatialized ideas of modernity. The trauma that workers experienced in the 1990s is most productively understood vis-à-vis the unfulfilled promises of "progress" which claimed to bring efficiency, growth, and long-term stability but instead delivered job loss, atomization, and the breakdown of social relations of labor.